Expression and processing of recombinant sarafotoxins precursor in Pichia pastoris - Borgheresi, RAMB; Palma, Mario Sergio [UNESP]; Ducancel, F.; Camargo, ACM; Carmona, E. (Elsevier B.V., 2001)
Sarafotoxins are peptides isolated from the Atractaspisw snake venom. with strong constrictor effect on cardiac and smooth muscle. They are structurally and functionally related to endothelins. The sarafotoxins precursor cDNA predicts an unusual structure 'rosary-type', with 12 successive similar stretches of sarafotoxin (SRTX) and spacer, in the present work, the recombinant precursor of SRTXs was sub-cloned and expressed in the yeast Pichia pastoris. and secreted to the culture medium, Characterization by SDS-PAGE, immunoblot, mass spectrometry and biological activity, suggests that intact precursor was expressed but processing into mature toxins also occurred. Furthermore, our results indicate that the correct proportion of sarafotoxin types as contained in the precursor, is obtained in the yeast culture medium. Contractile effects of the expressed toxins, on rat and Bothrops jararaca isolated aorta, were equivalent to 5 X 10(-10) M and 5 x 10(-11) M of sarafotoxin b, respectively. The enzymes responsible for the complete maturation of sarafotoxins precursor are still unknown. Our results strongly suggest that the yeast Pichia pastoris is able to perform such a maturation process. Thus, the yeast Pichia pastoris may offer an alternative to snake venom gland to tentatively identify the molecular process responsible for SRTXs release. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: sarafotoxins; precursor of safarotoxins; processing enzymes; expression in Pichia pastoris